2017
DOI: 10.1111/cea.12878
|View full text |Cite
|
Sign up to set email alerts
|

Chronic airway inflammation provides a unique environment for B cell activation and antibody production

Abstract: Background B cells play many roles in health and disease. However, little is known about the mechanisms that drive B cell responses in the airways, especially in humans. Chronic rhinosinusitis (CRS) is an inflammatory disease of the upper airways that affects 10% of Europeans and Americans. A subset of CRS patients develop nasal polyps (NP), which are characterized by type 2 inflammation, eosinophils and group 2 innate lymphoid cells (ILC2). We have reported that NP contain elevated levels of B cells and antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 24 publications
7
50
0
1
Order By: Relevance
“…40,42 However, Feldman and collaborators did not detect an elevation of follicles or large clusters of lymphoid cells in their studies in Chicago. 43 In addition, large increases in extrafollicular plasmablasts expressing the marker Epstein-Barr virus-induced protein 2 have been reported by Hulse and her colleagues, suggesting that some B cells are activated outside of germinal centers in CRS tissues. 43 This could result in the emergence of autoreactive antibody producing cells, as reported by Tan et al 44 Whether the causative antigens driving local immunoglobulin production in nasal polyps are exogenous or self antigens or both has not been completely clarified.…”
Section: Immune Polarization In Crsmentioning
confidence: 94%
See 1 more Smart Citation
“…40,42 However, Feldman and collaborators did not detect an elevation of follicles or large clusters of lymphoid cells in their studies in Chicago. 43 In addition, large increases in extrafollicular plasmablasts expressing the marker Epstein-Barr virus-induced protein 2 have been reported by Hulse and her colleagues, suggesting that some B cells are activated outside of germinal centers in CRS tissues. 43 This could result in the emergence of autoreactive antibody producing cells, as reported by Tan et al 44 Whether the causative antigens driving local immunoglobulin production in nasal polyps are exogenous or self antigens or both has not been completely clarified.…”
Section: Immune Polarization In Crsmentioning
confidence: 94%
“…43 In addition, large increases in extrafollicular plasmablasts expressing the marker Epstein-Barr virus-induced protein 2 have been reported by Hulse and her colleagues, suggesting that some B cells are activated outside of germinal centers in CRS tissues. 43 This could result in the emergence of autoreactive antibody producing cells, as reported by Tan et al 44 Whether the causative antigens driving local immunoglobulin production in nasal polyps are exogenous or self antigens or both has not been completely clarified. In Caucasian patients with CRSwNP, it has been reported that Staphylococcus aureus enterotoxins, acting as both antigens and superantigens, may drive local IgE production.…”
Section: Immune Polarization In Crsmentioning
confidence: 94%
“…96 In humans, ILC2 promote B cell extrafollicular responses as evidenced by increased B cell expression of EBI2 in human ILC2:B cell co-culture. 97 These data suggest ILC2 may influence the B cell and/or IgE compartments in allergic disease. 98 ILC2 also coordinate with cells of the innate immune system.…”
Section: Ilc2 Mechanisms Of Pathogenesis In Allergic Diseasementioning
confidence: 88%
“…Экстрафолли-кулярный антительный ответ характерен для ран-ней стадии инфекционного процесса и может осу-ществляться с помощью или без помощи Т-клеток [19]. Экстрафолликулярные плазматические клетки являются короткоживущими клетками и не обес-печивают долгосрочной продукции антибактери-альных антител.…”
Section: рисунок 2 ингибирующее влияние бактерий Staphylococcus Aureunclassified